Effect of phorbol 12-myristate 13-acetate treatment on choline kinase expression - Seong, Chan Ying (Universiti Sains Malaysia, 2012)
Choline kinase (CK) plays main role in the de novo phospholipid synthesis pathway. It phosphorylates choline into phosphocholine in the presence of ATP and Mg2*. Many studies have showed that the carcinogenesis and tumorigenesis are associated with the increased of CK and it has become the hallmark of cancerous cells. It is so importantly that CK has become the potential target of the anti-cancer therapy. Yet, studies on the promoter sequence of the CK remain rare. In order to identify the potential transcription factor binding sites which act on regulating the CK promoter, -1252 to -1275 of choline kinase a, (hCKa) promoter sequence was investigated for the effect of phorbol 12-myristate 13-acetate (PMA) treament in human breast adenocarcinoma cell lines, MCF-7. A -1284 putative promoter of CKa was cloned into a luciferase (Luc) based reporter vector system. In MCF-7 cells, PMA treatment decreased the expression of Luc under the control of the CKa promoter. In addition, CKa mRNA and protein levels were decreased compare to the control in response to the PMA treatment. PMA, the protein kinase C (PKC) activator, promoted the E26 transformation specific sequencec, Ets family transcription factors activity. The results suggest that cEts family transcription factors were acting as negative regulators of CKa promoter activity.